Integrase Strand Transfer Inhibitors (INSTIs) Resistance Mutations in HIV-1 Infected Turkish Patients. Issue 3 (3rd May 2016) - Sayan, M.; Gündüz, A.; Ersöz, G.; İnan, A.; Deveci, A.; Özgür, G.; Sargın, F.; Karagöz, G.; İnci, A.; İnan, D.; Ülçay, A; Karaoğlan, İ.; et al.
Abstract : Objectives : Integrase strand transfer inhibitor (INSTI) is a new class of antiretroviral (ARV) drugs designed to block the action of the integrase viral enzyme, which is responsible for insertation of the HIV-1 genome into the host DNA. The aim of this study was to evaluate for the first time INSTI resistance mutations in Turkish patients. Methods: This study was conducted in Turkey, between April 2013 and April 2015 using 169 HIV-1-infected patients (78 ARV naive patients and 91 ARV-experienced patients). Laboratory and clinical characteristics of ARV naive and ARV-experienced patients were as follows: gender (M/F): 71/7 and 80/11, median age: 38 and 38.4; median CD4 + T-cell: 236 and 216 cells/mm 3, median HIV-1 RNA: 4.95+E5 and 1.08E+6 copies/ml. Population-based seqeunces of the reverse transcriptase, protease, and integrase domains of the HIV-1 pol gene were used to detect HIV-1 drug resistance mutations. Result: INSTI resistance mutations were not found in recently diagnosed HIV-1-infected patients. However, ARV-experienced patients had major resistance mutations associated with raltegravir and elvitegravir; the following results were generated:F121Y, Y143R, Q148R and E157Q (6/91 – 6.6%). Conclusions: The prevalence of INSTI resistant mutations in ART-experienced patients suggested that resistance testing must be incorporated as an integral part of HIV management with INSTI therapies.